Pemberlakuan Syari'at Islam di Indonesia - Mushlihin, Imam Annas (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
UU No. 22/1999 about Regional is one factor triggering the high demand of maintaining Islamic law. It is such on opportunity to uphold the Islamic law. Some theories e.g reception in complex, receptive, receptie exit and reception a contario has influenced some new regulation. In political point of view, the upholding of Islamic law is mainly caused by strong moslem’s politic-religy. Some areas put regional regulation into effect and it causes some discourse counter by using human right norms.